2014
DOI: 10.1002/adma.201401194
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically Designed SiOx/SiOy Bilayer Nanomembranes as Stable Anodes for Lithium Ion Batteries

Abstract: Hierarchically designed SiOx /SiOy rolled-up bilayer nanomembranes are used as anodes for lithium-ion batteries. The functionalities of the SiO(x,y) layers can be engineered by simply controlling the oxygen content, resulting in anodes that exhibit a reversible capacity of about 1300 mA h g(-1) with an excellent stability of over 100 cycles, as well as a good rate capability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
111
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(114 citation statements)
references
References 35 publications
(34 reference statements)
1
111
0
1
Order By: Relevance
“…Reproduced with permission. [ 267 ] wileyonlinelibrary.com vapor deposition of by using solution coating) and allows for a better control over the thickness and morphology of the battery layers. There are several examples in the literature that have approached this fabrication.…”
Section: Wileyonlinelibrarycommentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced with permission. [ 267 ] wileyonlinelibrary.com vapor deposition of by using solution coating) and allows for a better control over the thickness and morphology of the battery layers. There are several examples in the literature that have approached this fabrication.…”
Section: Wileyonlinelibrarycommentioning
confidence: 99%
“…[ 266 ] Using similar sacrifi cial layer techniques, Zhang et al fabricated multi-layer Si-based coiled nanomembranes and found them suitable for negative electrode for lithium batteries (Figure 9 F). [ 267 ] Ji et al made Swiss roll membranes as small as 5 µm in diameter and characterized their supercapacitive behavior. [ 280 ] Similarly, Sharma et al designed large area, rolled-up nanomembrane-based capacitor arrays by combining bottom-up and top-down fabrication methods.…”
Section: Wileyonlinelibrarycommentioning
confidence: 99%
“…However, one of the major drawbacks of silicon is the ~300% volumetric change upon charging and discharging, which results in peeling and pulverization of the electrode and eventual capacity loss. Numerous works have been carried out to address these issues, such as using nano-enabled silicon structures, preparing Si/C composites to improve electric conductivity and constructing porous structure or compositing with other active/non-active matrix to buffer the volume change [30,31,32,33]. Considering the structure stability of LTO, it is expected that LTO can also alleviate some of the volumetric expansion of silicon during the cycling process by acting as a buffer.…”
Section: Introductionmentioning
confidence: 99%
“…Rolled‐up technology has recently proven to be an efficient method on micro/nanoscale for promising future applications. With rolled‐up technology, it is convenient to prepare single‐layered or multilayered composite membranes with well‐controlled thicknesses, stacking sequence, and chemical composition 21. Moreover, structure stability can be maintained by self‐winding to release the intrinsic strain accommodated in the membranes 21.…”
mentioning
confidence: 99%
“…With rolled‐up technology, it is convenient to prepare single‐layered or multilayered composite membranes with well‐controlled thicknesses, stacking sequence, and chemical composition 21. Moreover, structure stability can be maintained by self‐winding to release the intrinsic strain accommodated in the membranes 21. With such new type of hybrid cathode configuration based on trilayered Pd/MnO x /Pd nanomembranes, the power efficiency of Li‐O 2 batteries was greatly improved from ≈60% to ≈86%, as compared to the bare MnO x nanomembranes.…”
mentioning
confidence: 99%